Prevalence and etiological classification of thrombocytopenia among a group of pregnant women in Erbil City, Iraq - Rawand Pouls Shamoon; Nawsherwan Sadiq Muhammed; Muhammed Salih Jaff (Turkish Journal of Hematology, 2009)
Objective: To determine the prevalence and define the causes of pregnancy-associated thrombocytopenia. Materials and Methods: A total of 850 pregnant women at different ages of gestation were screened for thrombocytopenia. A control group of 150 age-matched non-pregnant women were tested for platelet count. Newborns of thrombocytopenic women were tested within 24 hours of delivery and reassessment of the women's platelets was done within 7-10 days post-delivery. Results: The mean platelet count in pregnant women was significantly lower than in non-pregnant women (221±59.9/mm3 vs. 273±66.9/mm3). Thrombocytopenia affected 8% of cases, with peak incidence during the third trimester. Gestational thrombocytopenia was found to be the principal cause (73.8%); hypertensive disorders caused thrombocytopenia in 23% of cases and two cases (4%) were due to immune thrombocytopenic purpura. No maternal or fetal complications were noted. The mean platelet count of 51 newborns of thrombocytopenic women was 240±7.1. Two newborns (4%) had low platelet counts. Conclusion: The majority of thrombocytopenias were mild gestational and occurred in late pregnancy. No maternal or neonatal bleeding complications were observed.